Metode Pembelajaran PAI Tingkat Sekolah Dasar - Maharani, Bintang; Rahman, Rini (Lembaga Yasin AlSys, 2025)
Failure in instructional strategies is often caused by a mismatch between the methods used and students’ needs and learning styles, ultimately hindering content comprehension. This study aims to analyze the instructional strategies used in Islamic Religious and Character Education within the implementation of the Merdeka Belajar Curriculum at SD Angkasa Lanud Sutan Sjahrir, Padang City, and to identify the supporting and inhibiting factors involved. The research employed a qualitative approach, with data collection techniques including observation, interviews, and documentation involving the principal, Islamic Religious Education teacher, and students. The findings indicate that instructional strategies were systematically designed, encompassing the formulation of learning objectives, stages of activity (introduction, core, and closing), selection of relevant methods, and the use of engaging media. The learning objectives were focused on developing students’ knowledge and character, while the chosen methods and media effectively enhanced student participation and learning enthusiasm. Supporting factors for the implementation of these strategies included the involvement of all school elements and the availability of adequate facilities, while inhibiting factors included limitations in resources and time. Overall, the instructional strategies for Islamic Religious and Character Education in the implementation of the Merdeka Belajar Curriculum have been effectively applied through appropriate method and media selection and the active involvement of teachers and students in the learning process. This has had a positive impact on instructional effectiveness and the achievement of curriculum goals.